Mutations in Van Der Woude Families From Ethiopia. Issue 2 (13th March 2022) - Eshete, Mekonen; Alade, Azeez; Abate, Fikre; Mossey, Peter A.; Awotoye, Waheed A.; Busch, Tamara; Hailu, Abiye; Demissie, Yohannes; Butali, Azeez
Abstract : Background: Van der Woude syndrome (VWS) is the most common syndromic orofacial cleft which accounts for approximately 2% of all cleft lip (CL) and/or palate cases. It is characterized by the presence of lower lip pits, in addition to CL, CL with or without cleft palate, cleft palate only, and hypodontia. It is inherited as an autosomal-dominant trait with almost complete penetrance but variable expressivity, and different variants in IRF6 gene have been reported in different populations around the world including African populations (Ethiopian, Ghanaian, and Nigerian). Methods and Findings: The authors investigated the role of IRF6 in Ethiopian families with VWS. The DNA of 7 families with VWS from Ethiopia were screened by Sanger sequencing. The authors screened all 9 exons of IRF6 and found a novel missense variant in exon 4 (p. Gly65Glu). This variant was predicted to be deleterious/probably damaging by Sift and PolyPhen, respectively. The IRF6 variant (p. Gly65Glu) segregates in the family since it was identified in the father and a sibling. Conclusion: Several of the individuals with lower lip pits in this study did not seek treatment. This is due to lack of awareness about the significance of this minor looking deformity and its consequences, and availability of treatment for birth defects. Therefore, it is important to educate families. Finally, screening for novel variants in known genes has a role in counseling and prenatal diagnosis for high-risk families.